Soft Magnetic Sensor Array for Amphibious Measurement of 3D Muscle Deformation Distribution for Human Motion Recognition - Liu, Yuchao; Chen, Zihan; Guo, Chuxuan; Liu, Zijie; Chen, Yibin; Wu, Xuan; Li, Zhuo; Wang, Qining; Guo, Jiajie (Advanced intelligent systems, 2025)
Skeletal muscles are the primary power source for voluntary limb joint motions, thus muscle deformation (MD) is vital to reflect human motions. However, most sensors can capture only 1D MD features, and are suitable only for on‐land scenarios, leading to the under evaluation and under exploitation of MD sensing. This article develops a 4 × 4 soft magnetic sensor array (SMSA) to capture 3D MD distribution. Compared to solid structures, the used porous elastomer mitigates hydraulic pressure disturbances by half within 0–100‐m water depth, while sensitivity increases by 10 times. The SMSA has consistent amphibious measurements and about 200 ms faster response than inertial measurement units (IMUs). Mapping between 3D magnetic flux densities and deformations of elastomers is justified by calibration errors within 1% of full ranges. Experiments justify the proposed method in multiple environments, muscles, motions, and subjects. Average gait classification accuracy is 98.73%, and phase estimation error is 2.85% when using only one SMSA, which is better than existing commercial sensors (with 82.40% and 10.39% for one IMU, and 89.06% and 6.33% for one flexible resistive sensor array). The proposed method can contribute to muscle state monitoring for human–machine interaction, rehabilitation engineering, and sports science.